Mitochondrial quality control alterations and placenta-related disorders - Wu, Yamei; Li, Meng; Ying, Hao; Gu, Ying; Zhu, Yunlong; Gu, Yanfang; Huang, Lu (Frontiers in Physiology, 2024)
Mitochondria are ubiquitous in eukaryotic cells. Normal maintenance of function is the premise and basis for various physiological activities. Mitochondrial dysfunction is commonly observed in a wide range of pathological conditions, such as neurodegenerative, metabolic, cardiovascular, and various diseases related to foetal growth and development. The placenta is a highly energy-dependent organ that acts as an intermediary between the mother and foetus and functions to maintain foetal growth and development. Recent studies have demonstrated that mitochondrial dysfunction is associated with placental disorders. Defects in mitochondrial quality control mechanisms may lead to preeclampsia and foetal growth restriction. In this review, we address the quality control mechanisms of mitochondria and the relevant pathologies of mitochondrial dysfunction in placenta-related diseases, such as preeclampsia and foetal growth restriction. This review also investigates the relation between mitochondrial dysfunction and placental disorders.